A semântica argumentativa em análise de compreensão do sentido em questões de língua inglesa do ENEM - Rio, Marlon Machado Oliveira (2016)
The present dissertation aims to analyze the English language questions in ENEM by using the Argumentation Within Language (AWL) theory made by Oswald Ducrot, Marion Carel and collaborators. As its main goal, it is aimed at proposing a reading concept under the ANL theoretical background and investigating in which way this theory may display the meanings within the discourse in order to help in the referred exam questions comprehension. As this national exam has received a careful attention in the last couple of years, since it is an exam which demands from its candidates the comprehension of key-texts, being the ones which are several times enough for choosing the most suitable answer, it is believed that the analysis of the ENEM English language questions enables a considerably fruitful window of opportunity for study, once the discourse made by the key-texts of the questions leads the candidate to choose only one alternative, which corresponds to the discourse produced in the key text, being the other ones from the other alternatives not authorized. The ANL theory is an argumentative semantics theory and analyzes the meaning of utterances in the linguistic level by using semantic blocks. The primary objective here is to analyze the construction of meaning in the utterances of the exam questions, so that it may be possible to find the most suitable answer in the linguistic level, using the analysis of produced discourses in the key-texts, comparing the argumentative chaining and semantic blocks to the alternatives and the correct answer. This dissertation aimed at doing it based on the linguistic level in order to understand the meaning production in the discourse level. According to Ducrot, the nature of language is essentially argumentative and not informative, since argumentation is the principle that directs linguistic production.